Terezín [videorecording (DVD)] - Speranza, Ennio; Zannon, Alessandro; Guidi, Gabriele; Conte, Mauro; Zelenikova, Dominika; Boni, Alessio; Dobry, Karel (Vantage Media, 2026)
Antonio, an Italian clarinettist, and Martina, a Czechoslovak violinist, fall in love with each other during the World War II, in Prague. Shortly afterwards they are deported to Terezin concentration camp.